Third-Party Funding in International Investment Arbitration - Adnan Tarık Doğan (Public and Private International Law Bulletin)
The use of third-party funding in international investment arbitration has increased significantly in recent years. In thirdparty funding, funders finance a legal claim in which they have no pre-existing interest with the aim of receiving financial benefit. In this way, the funded party avoids paying arbitration costs. If the case is lost, the funded party additionally doesn’t have to make any repayments to the funder. The right to access to justice is established because of the arbitration costs covered by the funder. Third-party funding also provides significant contributions with regard to sharing with the funder the risks of costs that may arise during the tribunal. One should note that funders are very selective about financing disputes and reject 90% of applications if they don’t see a high chance of success. In order to provide funding, a funding agreement must be signed between the funded party and the third-party funder. Although the legal character of this agreement is controversial in terms of doctrine, considering it as sui generis has been concluded to be beneficial.Third-party funding also has negative effects on the tribunal process in international investment arbitration. The presence of a third-party funder can raise doubt as to the impartiality and independence of the arbitrators. With the 2022 Amendment of the ICSID Arbitration Rules, a major step has been taken by making a new rule about disclosure of third-party funding. Another negative effect of third-party funding is that the funder may want to take full control over the arbitral proceeding. The last part of the study evaluates security for costs when a third-party funder is present.